"Взят на изученіе майстерству без заплати": ремісниче учнівство в містах Гетьманщини (на прикладі Ніжина 1760-х років) - Коваленко, О. (Краєзнавство, 2018)
У статті розглянуто основні етапи ремісничого учнівства (здійснено підрахунки кількості учнів
у майстра, встановлено віковий діапазон учнів, проведено кореляцію наявності учнів із наявністю власних дітей у родині ремісника). Аналіз проведено на основі Генерального опису Лівобережної України
м. Ніжина, здійсненого там у 1766 р., із залученням даних інших міст Гетьманщини. Prime sources of this theme is the General Description of the Left-bank Ukraine – especially historicaldemographic
facts of the Nizhyn 1766 y. Then there were 5086 inhabitants in the city, including 282 craftsmen,
which worked in guildes and outside of it, working as «piddani» (serves), or «under protection». In the city at
that, time was 30 specialties. The first stage of acquiring the status of full masters was apprenticeship. About
20% craftsmen of the of Nizhyn trained the apprentices of the craft. 1-4 apprentices could live in the family of
the master, simultaneously. Craft apprenticeship lasted from 1 till 10 years. Predominantely 4-5 years. The age
of the apprentices was from 5 till 19 years. Predominantely 10-15 years. Division masters according to presence
of sons and/or apprentices showed that in the presence of their own sons, the masters in most did not take apprentices
to study, and childless men, by contrast, sought to bring apprentices to the family. The importance of
playing a role of father, patriarch, and head of the family caused that for master apprenticeship was not only
economic way to develop his household, but some specific replacement of missed parenting. Division masters
according to presence of sons and/or apprentices. For apprentice that was a stage of life cycle service, after
which he received specialization, new social status, and could create his own household and ply a craft. В статье рассмотрены основные этапы ремесленного ученичества (осуществлены подсчеты количества учеников у одного мастера, установлен возрастной диапазон учеников, проведена корреляция
наличия учеников с наличием собственных детей в семье ремесленника). Анализ проведен на основе
Генерального описания Левобережной Украины г. Нежина, проведенного там в 1766 г., в сравнении с данными других городов Гетманщины.